MANAJEMEN KURIKULUM INTEGRATIF MADRASAH - PESANTREN (Studi Multisitus di MAN 1 Malang dan Madrasah Terpadu MAN 3 Malang) - Muhammad Rouf (Al Hikmah: Jurnal Studi Keislaman, 2016)
Mulyasa worries this decline is an evidence of a shift towards value destruction, or the creation of new values based on pragmatism, materialism, hedonism, secularism, even atheism. In forming the character or noble character, Indonesia has long been a successful model of education, formed the character of the nation's children in the education system of "pesantren". Therefore, the combination of schools into the formal education system—such as school and madrasah—became important to apply today. The purposes of this study are to describe the integrative curriculum planning of madrasah-pesantren, to describe the implementation of an integrative curriculum of madrasah-pesantren in MAN 1 Malang and Madrasah Terpadu MAN 3 Malang, and to describe an integrative curriculum evaluation of madrasah-pesantren in MAN 1 Malang and Madrasah Terpadu MAN 3 Malang. This study uses a qualitative approach with case study by the unit of analysis of compound cases or multi-site studies. The data collection is conducted with participatory observation, interview, and documentation. Data analysis uses data reduction techniques, data presentation, and conclusion and verification. The results of the research in MAN 1 Malang and Madrasah Terpadu MAN 3 Malang are: 1) integrative curriculum plannings of madrasah-pesantren are applied by: a) curriculum objectives integration and b) integration of organization of curriculum content. 2) Implementations of integrative curriculum madrasah-pesantren are done by: a) integration of program implementation of the curriculum and  b) integration of curriculum implementation supervision. 3) Evaluation of integrative curriculum madrasah-pesantren is done by evaluate the curriculum in coordination between madrasah-pesantren, which include: a) evaluation of curriculum context, b) evaluation of curriculum input, c) evaluation of curriculum process and d) evaluation of the curriculum products.